Does a Code for Acute Myocardial Infarction Mean the Same in All Norwegian Hospitals? A Likelihood Approach to a Medical Record Review - Helgeland J; Kristoffersen DT; Skyrud KD (Clinical Epidemiology, 2022)
Jon Helgeland, Doris Tove Kristoffersen, Katrine Damgaard Skyrud Division for Health Services, Norwegian Institute of Public Health, Oslo, NorwayCorrespondence: Jon Helgeland, Norwegian Institute of Public Health, PO Box 222 Skøyen, Oslo, 0213, Norway, Tel +47 464 00 443, Email Jon.Helgeland@fhi.noObjective: Health registries are important data sources for epidemiology, quality monitoring, and improvement. Acute myocardial infarction (AMI) is a common, serious condition. Little is known about variation in the positive predictive value (PPV) of a coded AMI diagnosis and its association with hospital quality indicators. The present study aimed to investigate the relationship between PPV and registry-based 30-day mortality after AMI admission and between-hospital variation in PPV.Study Design and Setting: An electronic record review was performed in a nationwide sample of Norwegian hospitals. Clinical signs and cardiac troponin measurements were abstracted and analyzed using a mixture model for likelihood ratios and parametric bootstrapping.Results: The overall PPV was estimated to be 97%. We found no statistically significant association between hospital PPV and the classification of hospitals into low, intermediate, and high registry-based 30-day mortality. There was significant variation between hospitals, with a PPV range of 91– 100%.Conclusion: We found no evidence that variation in PPV of AMI diagnosis can explain variation between hospitals in registry-based 30-day mortality after admission. However, PPV varied significantly between hospitals. We were able to use a very efficient statistical approach to the analysis and handling of various sources of uncertainty.Keywords: health registries, quality indicators, finite mixture models, case fatality, cardiac troponins